O ensino da geografia e sua especificidade na base nacional comum curricular brasileira: uma cartografia das ausências - Ozório, Augusto Monteiro (2018)
The teaching of Geography has always been present in the official curriculum of Brazillian basic school. However, since its institutionalization, it has been through moments of greater or lesser relevance among other school subjects. Recently, BNCC (Base Nacional Comum Curricular – the institucional norm which defines the official basic curriculum) is being redefined and, as a result, it is possible that Geography will no longer be applied as a required and mandatory subject in Secondary School, which reveals, among other factors, that we are in front of a context of devaluing this subject in the group of knowlegde believed to be necessary and basic to insert individuals in western, urban-industrial society. The objective is to understand the reasons that led to the loss of relevance of Geography as a subject in the official curriculum. To accomplish that, a bibliographical research was done on the role of teaching systems in the curricular organization and the renovation movement of brazillian geographical thinking experienced since the end of the 1970s. As a result, it was verified, from a greater generalization scale, that a neoliberal context reoriented the brazillian teaching system to adhere to aspects of an utilitarian notion of curriculum, one that do not see geographical knowledge as utmost relevant to insert individuals on the model of society that is intended. At the same time, in a more-detailed scale, the loss of importance was also due to the difficulty from the people who inherited the fruits of the renewal movement to unite themselves and/or disseminate the speech about the methodology and epistemology of geographic science to the pedagogical speech under the geographical teaching in the school environment, especially from the renewal movement about geographic thinking experienced by the second half of 20th Century in Brazil